(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2026)
This study investigates the optimization of heating a 30% oil-70% gas condensate mixture in the industrial shell-and-tube heat exchanger-condenser 10E-04 at the Bukhara Oil Refinery. The mixture flow rate was 105,508 kg/h, with an inlet temperature of 96.1°C and a naphtha vapor condensation temperature of 136.6°C. A refined mathematical model accounting for temperature-dependent changes in density (768- 744 kg/m3), heat capacity (2180-2310 J/kg·°C), and viscosity (0.0032-0.0023 Pa·s) was applied, improving calculation accuracy by 20-30%. The overall heat transfer coefficient was 270 W/m2·K. Analysis showed that at the regulated outlet temperature of 111.7°C, only 72% of the 273 m2 heat transfer surface is effectively utilized. The optimal outlet temperature was determined as 107.3°C, corresponding to a required surface of 220 m². At this condition, pump power consumption is 15.4 kW and the minimum specific technological cost is 285.12 sum/kg. The optimized regime reduces effective heat transfer surface by 19% and lowers technological costs by approximately 3-4%, revealing additional thermal capacity reserves of the apparatus.